(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2020)
This paper describes the concept of “soft power” from the American foreign policy perspective. Nowadays, the concept of “soft power” is increasingly described not only in politics, but also in many other spheres of social life by and large. The International Community is faced with it even in the most ordinary situations, such as: cultural exchange, study abroad, trade, language learning, media as well as social networks, and many others. Today, this concept has become a powerful tool for integrating countries through non-coercion and the use of traditional force. On the contrary, “soft power” has come to be described as the most effective instrument for gaining confidence in the current “balance of power” and the “presence of nuclear weapons”. The United States is the founder and vivid example of the concept “soft power” implementation into the practice. This concept has been most successfully applied in foreign policy by President Barack Obama. Today, International Community is witnessing a dramatic change in foreign policy with the change of the United States administration from Obama to Trump in 2016.